Gastric Cancer associated with the use of Omeprazole in Adults - Aviza Joaquín, Ariel Aníbal; Sabattini, Analía Claudia (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: proton pump inhibitors constitute a group of drugs used to suppress stomach acid secretion and whose consumption has intensified worldwide due to their consideration as the most effective gastric protectors, omeprazole being one of the most widely used. Objectives: to analyze the existence of gastric cancer risk due to long-term use of omeprazole in adults.Methods: a search for information was carried out in PubMed and Google Scholar. Search formulas were used by combining the terms: “Omeprazole”, “Cancer Gastric”, “Omeprazole and Adverse effects”, “Omeprazole and Helicobacter Pylori”. From the total number of articles identified, after the screening process, 8 articles were chosen for the present study.Results: Prolonged treatment with omeprazole can induce histological changes in the gastric mucosa, including hyperplasia, increased gastrin-producing cells, atrophic gastritis and increased colonization of Helicobacter pylori. A rebound acid hypersecretion has been observed after discontinuation of treatment, persisting for at least two months. Endocrine hyperplasia may result from suppression of acid secretion, causing hypergastrinemia and increasing the risk of malignant lesions.Conclusions: information has been compiled on the effects of prolonged use of omeprazole and its relationship with gastric carcinoma. This use is becoming more frequent, which underlines the need to investigate its long-term effects, since it may alter gastric histoarchitecture and predispose to cancer